An adaptive droop control for distributed battery energy storage systems in microgrids with DAB converters. (September 2021) - Xing, Wei; Wang, Hewu; Lu, Languang; Wang, Shuoqi; Ouyang, Minggao
Highlight: An adaptive droop control method considering battery power characteristics is proposed. Virtual battery droop algorithm is combined with the battery online estimation. Suitable power distribution for batteries is realized in a decentralized way. SOC balancing among energy storage systems can be achieved. The proposed control is applied on the microgrid model with DAB converters. Abstract: With the progress of renewable energy technologies, distributed energy system (DES) has become attractive due to its flexibility and interaction with power systems. Battery energy storage system (BESS) is an indispensable part of DESs, the control strategies of which have a great influence on system performance. In this paper, we present a novel adaptive droop control (ADC) for energy storage batteries. The state and model parameters of energy storage batteries are estimated simultaneously online by dual extended Kalman filter (DEKF) algorithm. Then the droop controller is designed based on the battery parameters by the "virtual battery" algorithm, benefit from which power can be distributed among battery packs adaptively for their power characteristics, meanwhile SOC balancing can be achieved automatically. The proposed control strategy is validated in MATLAB/Simulink environment with a direct-current (DC) microgrid model where battery packs are connected to the DC bus through dual active bridge (DAB) converters. Compared with conventional droop controls, the proposed ADC method considers the battery characteristics and battery aging, and it is more suitable for DES with multiple sets of batteries.